Global Dynamics of a Nonlinear Beam Equation with Strong Structural Damping (Journal of Partial Differential Equations, 2020)
In this paper, the global attractor, exponential attractor and flat inertial manifold are obtained for a nonlinear beam equation with strong structural damping.
Keywords: Nonlinear beam equation; global attractor; exponential attractor; flat inertial manifold